2016
DOI: 10.1124/dmd.116.070151
|View full text |Cite
|
Sign up to set email alerts
|

Application of Osmotic Pumps for Sustained Release of 1-Aminobenzotriazole and Inhibition of Cytochrome P450 Enzymes in Mice: Model Comparison with the Hepatic P450 Reductase Null Mouse

Abstract: The effectiveness of controlled release 1-aminobenzotriazole (ABT) administration to inhibit cytochrome P450 (P450) enzymes has been evaluated in mice. To maximize the duration of P450 inhibition in vivo, ABT was administered via an osmotic pump. The degree of P450 inhibition was compared with that achieved with a single bolus dose of ABT. Two-hour prior subcutaneous treatment of mice with ABT (50 mg/kg) inhibited antipyrine clearance by 88%. A less pronounced inhibitory effect (29% reduction in clearance) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…CYP2C9 was particularly resistant to inhibition by ABT, with 60% of the activity remaining. A separate study indicated that ABT caused a concentration-dependent inhibition of CYP1A2, -2B6, -2C9, -2C19, -2D6, and -3A4 [25]. Taken together, our results suggest that CYP2C9 or -2C8 may be responsible for the metabolism of the benzo[ d ][1,3]dioxol-4-yl group of 9 and 14 in MLM.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…CYP2C9 was particularly resistant to inhibition by ABT, with 60% of the activity remaining. A separate study indicated that ABT caused a concentration-dependent inhibition of CYP1A2, -2B6, -2C9, -2C19, -2D6, and -3A4 [25]. Taken together, our results suggest that CYP2C9 or -2C8 may be responsible for the metabolism of the benzo[ d ][1,3]dioxol-4-yl group of 9 and 14 in MLM.…”
Section: Resultssupporting
confidence: 52%
“…Long-term dosing of ABT is also possible. ABT has displayed a well-behaved pharmacokinetic profile over five days when dosing with an osmotic pump [25]. Minimal side effects were observed for chronic ABT dosing, the most prominent of which was delayed gastric emptying [33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, ABT displayed a well-behaved pharmacokinetic profile over 5 days dosing via osmotic pump. 24 Minimal side effects were observed on chronic ABT dosing, the most prominent of which is gastric emptying. 25 Second, there is potential for 1 and ABT to be utilized in species other than mice in in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that 1-ABT delays gastric emptying in rats and can alter systemic exposure and T max of coadministered agents [ 30 ]. The observation that 50 mg/kg of 1-ABT inhibited antipyrine clearance by 88% when given shortly before the antipyrine, but only by 29% when given 24 h before, suggested that the duration of 1-ABT was relatively short [ 31 ]. However, The pharmacokinetic profiles of oral doses of 1-ABT ranging from 5 to 200 mg/kg, determined in rats, dogs, and monkeys, showed that a single dose of 50 mg/kg in rats and 20 mg/kg in dogs and monkeys produced high plasma concentrations that were sustained over 24 hours [ 32 ].…”
Section: Metabolism and Pharmacokinetics Of 1-abtmentioning
confidence: 99%
“…Administration of 1-ABT 2 hours before intravenous antipyrine decreased plasma antipyrine clearance by approximately 95% in mice and 84–95% in guinea pigs at all the doses of 1-ABT examined [ 33 ]. Osmotic pumps can be used to maintain maximum blood concentrations of 1-ABT for at least 6 days [ 31 ]. Indeed, ALZET osmotic pumps were able to maintain the 1-ABT plasma concentration above 4.1 mg/ml over 336 hours without overt toxicity [ 34 ].…”
Section: Metabolism and Pharmacokinetics Of 1-abtmentioning
confidence: 99%